Energy rationale for the Use of the Thermophilic Mode of Anaerobic Bioconversion of Liquid Organic Waste in the Climatic Conditions of the Russian Federation - Kovalev, Andrey A.; Kovalev, Dmitriy A.; Litti, Yuri V.; Katraeva, Inna V.; Nozhevnikova, Alla N. (KnE Life Sciences, 2022)
The transition of livestock production to industrial processes and the concentration of animals associated with this process on large farms and complexes has caused a sharp increase in the volume of manure that must be disposed of without pollution. One of the ways of processing organic waste (biomass) is its anaerobic digestion in biogas plants through the vital activity of microorganisms (methanogenesis).Biogas obtained using microbiological processing of biomass can be used as a raw material for heat and electric energy. Annually, 0.17% of the total livestock manure produced at Russian agricultural enterprisesis used for biogas production.The main component of a biogas plant is a manure fermentation reactor, the required volume of which is determined by the daily output of manure from the livestock farm, the temperature and the hydraulic retention time of treatment. This research explored thermal energy consumption of biogas plants, using the example of a biogas plant of a modular design that depended on the average annual outdoor temperature. Based on the calculations, the thermophilic mode was found to be more energy-efficient than the mesophilic one; thus, with the thermophilic mode, the specific energy consumption needed for the plant was lower at the average annual outdoor temperatures of all the constituent entities of the Russian Federation. At the same time, the specific biogas yield in the thermophilic regime was 20-50%higher than in the mesophilic regime. Keywords: anaerobic processing, agricultural waste, thermophilicmode, mesophilicmode, energy costs, energy rationale